Talent acquisition process: a detailed study on the effectiveness of initiatives taken by Arla Foods Bangladesh Limited - Arannya, Farhan Ahmed (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.